Age-stratified analysis of long-term outcomes of transvaginal mesh repair for treatment of pelvic organ prolapse. Issue 1 (October 2016) - Dong, Shengnan; Zhong, Yanbo; Chu, Lei; Li, Huaifang; Tong, Xiaowen; Wang, Jianjun
Abstract: Objective: To investigate long-term outcomes after transvaginal mesh repair among patients with pelvic organ prolapse in different age groups. Methods: A retrospective cohort study was conducted among women who underwent transvaginal mesh repair with polypropylene mesh for pelvic organ prolapse of stage II or higher between January 2007 and November 2011 at a center in Shanghai, China. Patients were invited to attend a follow-up appointment between July 2014 and May 2015. Surgical outcomes were compared among three age groups (≤ 59, 60–74, and ≥ 75 years), and quality-of-life questionnaires were evaluated. Multivariate logistic regression was used to identify risk factors associated with recurrent prolapse and mesh exposure. Results: Among 158 patients, 143 (90.5%) were objectively cured and 149 (94.3%) were subjectively cured at follow-up. Surgical outcomes were similar across all age groups. Significant improvements were observed on the Pelvic Floor Distress Inventory across all applicable subscales in all age groups ( P  < 0.001 for all). Multivariate logistic regression showed that an active postoperative sex life significantly increased the risk of mesh exposure (odds ratio 11.89, 95% confidence interval 1.08–131.48; P  = 0.043). Conclusion: Transvaginal mesh repair was found to be a safe and effective technique for treating pelvic organ prolapse among women of all ages. An active postoperative sex life increased the odds of mesh exposure.